Storage stability of pistachios as influenced by radio frequency treatments for postharvest disinfestations. (February 2016) - Ling, Bo; Hou, Lixia; Li, Rui; Wang, Shaojin
Abstract: There has been an increased interest in developing alternative physical methods for disinfesting postharvest nuts under growing international pressures to replace chemical fumigation due to its adverse effects on human health and environment. The present research explored the possibility of using radio frequency (RF) heating as a non-chemical treatment for disinfestations of pistachios. A pilot-scale, 27 MHz, 6 kW RF unit was used to study RF heating uniformity, develop a treatment protocol, and evaluate quality attributes and storage stability in treated samples. Only 5.6 and 5.5 min were needed to raise the centre temperature of 1.8 kg in-shell and 2.0 kg shelled pistachios to reach 55 °C using RF energy, respectively, compared to about 82 and 117 min when using hot air heating at 55 °C. RF heating uniformity in both types of pistachios was improved by adding forced hot air, sample movements on the conveyor and a single mixing in the middle of the treatment time. The final average temperatures on the surface and in the interior of both types of pistachio kernels exceeded 52 °C, following a holding step at 55 °C for 2 min using hot air. This provided a conservative and 100% mortality of fifth-instar Indianmeal moth ( Plodia interpunctella [Hübner]). RF treated samples were not significantly different from control samples in weight loss, peroxide values, fatty acid values, fatty acid composition and kernel colour. RF treatments can, therefore, potentially provide an effective and rapid protocol against stored product pests in pistachios as an alternative to chemical fumigation. Industrial relevance: A pilot-scale 6 kW RF system with conveyor belt was used to determine the heating uniformity and quality changes of pistachios. For a combination with hot air surface heating and mixing, an effective and continuous RF disinfestation method could be developed for pistachios. The RF heating technology has been successfully demonstrated for disinfesting walnuts in California, USA. We tried to expand the industrial applications of RF heating for disinfesting pistachios, to replace the chemical fumigation. This research may provide potential industrial applications of RF treatments for disinfestations based on fast and uniform heating. Highlights: RF heating uniformity was improved by forced hot air, movement, and mixing. Treatment protocol using RF energy was developed for disinfesting pistachios. Complete mortality of Indianmeal moth was confirmed with RF treatment protocol. Quality of pistachios before and after storage was not affected by RF treatments. RF heating provides effective and physical methods for disinfesting pistachios.